The applicability of eDNA metabarcoding approaches for sessile benthic surveying in the Kimberley region, north‐western Australia. Issue 1 (26th February 2021) - West, Katrina M.; Adam, Arne A. S.; White, Nicole; Robbins, William D.; Barrow, Daniel; Lane, Adrian; T. Richards, Zoe
Abstract: The application of environmental DNA technologies is a promising new approach to rapidly audit biodiversity across large‐scale, remote regions. Here, we examine the efficacy of a dual‐assay eDNA metabarcoding approach for sessile benthic bioassessments in the turbid waters of the Lalang‐garram marine parks, Kimberley, north‐western Australia. We ask three principal questions: (1) "Is the eDNA released by sessile benthic taxa (i.e., hard and soft corals, sponges and tunicates) locally detectable?", (2) "What level of taxonomic resolution is afforded by eDNA metabarcoding using the ITS2 region?", and (3) "How well does eDNA metabarcoding compare to conventional benthic survey techniques?". We report that a dual‐assay eDNA metabarcoding approach can detect approximately 70% of the local benthic taxa (i.e., at a species, genus level). It is, however, not as effective at the individual/population level, detecting only approximately 40% of unique amplicon sequence variant (ASV) signals released by an array of individual benthic organisms at the surveyed locations. In examining the efficacy and resolution of the applied ITS2 metabarcoding markers for bioassessments, we report large gaps in the variety of publicly available benthic ITS2 reference sequence data, limiting our ability to provide robust taxonomic assignments. These findings highlight the need to extend ITS2 databases for greater regional representation. Until this is adequately addressed, we recommend that investigating taxonomic assignments to a genus level is the most robust approach for benthic monitoring using eDNA. Lastly, we found eDNA metabarcoding and conventional belt transect surveys each detected numerous unique hard coral genera, indicating that a combined approach provides the most effective way to audit benthic biodiversity. This point notwithstanding, eDNA metabarcoding had the power to distinguish similar diversity trends between sites to that determined by the belt transect methodology, validating the application of eDNA metabarcoding as either a stand‐alone, or complementary technique for assessing sessile benthic taxa. Abstract : This study examines the efficacy of a dual assay eDNA metabarcoding approach for sessile benthic bioassessments in the turbid waters of the Lalang‐garram marine parks, Kimberley, north‐western Australia. We detected approximately 70% of the local benthic taxa however gaps in publicly available benthic ITS2 reference sequence data, limited our ability to provide robust taxonomic assignments at a species level. We recommend that investigating taxonomic assignments to a genus‐level is the most robust approach to benthic monitoring using eDNA.